2008
DOI: 10.1002/ajh.21126
|View full text |Cite
|
Sign up to set email alerts
|

Functional evidence for presence of lipid rafts in erythrocyte membranes: Gsα in rafts is essential for signal transduction

Abstract: Membrane microdomains enriched in cholesterol and sphingolipids and containing specific membrane proteins are designated as lipid rafts. Lipid rafts have been implicated in cell signaling pathways in various cell types. Heterotrimeric guanine nucleotide-binding protein (Gsa) has been shown to be a raft component of erythrocytes and has been implicated in cell signaling. Rafts are isolated as detergent-resistant microdomains (DRMs) for biochemical analysis. Cholesterol depletion is widely used to disrupt raft s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 32 publications
1
40
0
6
Order By: Relevance
“…Moreover, the inhibition of palmitoylation by 2-BrP treatment blocked adducin (a protein of ϳ90 kDa) phosphorylation in response to the G␣ s -mediated stimulation of PKA (supplemental Fig. S4D), which is known to be a palmitoylation and raft-dependent signaling pathway (37).…”
Section: Loss Of Palmitoylation Is Linked To Marked Decrease In Drm Fmentioning
confidence: 98%
“…Moreover, the inhibition of palmitoylation by 2-BrP treatment blocked adducin (a protein of ϳ90 kDa) phosphorylation in response to the G␣ s -mediated stimulation of PKA (supplemental Fig. S4D), which is known to be a palmitoylation and raft-dependent signaling pathway (37).…”
Section: Loss Of Palmitoylation Is Linked To Marked Decrease In Drm Fmentioning
confidence: 98%
“…Moreover, the gain of structure for disordered CTA1 is a raft-specific event. Because G s ␣ is present in lipid rafts (23)(24)(25)(26), CTA1 would benefit from the chaperonelike function of lipid rafts upon contact with its G protein target. The resulting gain of structure confers a basal level of activity to CTA1 without acting through allostery because no gain of function was recorded for CTA1 treated with lipid rafts at 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…G s ␣ is found in lipid rafts at the cytosolic face of the plasma membrane (23)(24)(25)(26). CTA1 would therefore encounter a lipid raft environment upon contact with its G s ␣ target.…”
Section: Cholera Toxin (Ct)mentioning
confidence: 99%
“…shown that the presence of Gs in the lipid rafts is essential for the Gs -mediated signal transduction 15) .…”
Section: Discussionmentioning
confidence: 99%